2011
DOI: 10.1016/j.conbuildmat.2010.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aggregates grading and water/cement ratio in workability and hardened properties of mortars

Abstract: Mortar is the material responsible for distribution of stresses in masonry structures. Knowledge about the fresh and hardened properties of mortar is fundamental to ensure a good performance of masonry walls. Water/cement ratio and aggregates grading are among several variables that influence physical and mechanical behaviour of mortars. An experimental program is presented in order to evaluate the influence of aggregates grading and water/cement ratio in workability and hardened properties of mortars. Eightee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(89 citation statements)
references
References 18 publications
8
71
0
10
Order By: Relevance
“…The WA allows the coalescence of foam bubbles inside the mortar, and consequently, an increase in the size of the bubbles and air content, which lessens density and CS. Results are in agreement with former studies by Nambiar and Ramamurthy [50] and Haach et al [49].…”
Section: Compressive Strength-cssupporting
confidence: 83%
See 1 more Smart Citation
“…The WA allows the coalescence of foam bubbles inside the mortar, and consequently, an increase in the size of the bubbles and air content, which lessens density and CS. Results are in agreement with former studies by Nambiar and Ramamurthy [50] and Haach et al [49].…”
Section: Compressive Strength-cssupporting
confidence: 83%
“…This shows that CDW granulometry has a significant influence upon CS by a contribution of 15%. Studies performed by Haach et al [49] also found a small influence of granulometry on CS; however, natural sand was used as aggregate. FS also significantly influenced CS by a contribution of 71%.…”
Section: Compressive Strength-csmentioning
confidence: 99%
“…Many scholars have conducted several research works on the effects of different parameters including water to cement (W/C) ratio, sand to cement (S/C) ratio and aggregate type S/Con the compressive strength and related factors such as porosity, workability and durability of mortar [14][15][16][17][18][19][20]. As instance, Singah et al studied the effect of W/C ratio on mechanical properties of cement mortar such as compressive and tensile strengths [14].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of different types of aggregates on the compressive strength of mortar was studied by Bumanis et al [16]. Snuck et al investigated the effect of W/C ratio and aggregate grade on the workability and hardened properties of mortar [20].…”
Section: Introductionmentioning
confidence: 99%
“…Cuando esto sucede, las probetas quedan completamente rellenas y la masa de mortero se distribuye con facilidad ocupando todo el molde evitando espacios internos, a priori esto es ventajoso, pero si el escurrimiento es excesivo puede debilitar en exceso la muestra obteniendo consecuencias contraproducentes [20].…”
Section: Ensayos Y Propiedades De Los Morteros Para Edificaciónunclassified